Multicystic and diffuse malignant peritoneal mesothelioma in children. Issue 6 (11th April 2020) - Vermersch, Sophie; Arnaud, Alexis; Orbach, Daniel; Andre, Nicolas; Berger, Claire; Kepenekian, Vahan; Brigand, Cécile; Fresneau, Brice; Poli‐Merol, Marie‐Laurence; Habougit, Cyril; Varlet, François; Scalabre, Aurélien
Abstract: Background: Malignant and multicystic peritoneal mesotheliomas are extremely rare tumors in children, developing from mesothelial cells. No specific guidelines are available at this age. Methods: We performed a retrospective analysis of all identified children (< 18‐year‐old) treated in France from 1987 to 2017 for a diffuse malignant peritoneal mesothelioma (DMPM) or a multicystic peritoneal mesothelioma (MCPM). Results: Fourteen patients (5 males and nine females), aged 2.2 to 17.5 years, were included. The most frequent presenting symptoms were abdominal pain, ascitis, and alteration in the general condition. Eight patients had epithelioid mesothelioma, three had biphasic mesothelioma, and three had MCPM. Eight patients with DMPM diagnosis received cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC). Among them, six patients had neoadjuvant systemic chemotherapy, one patient, post‐operative chemotherapy, and one patient CRS and HIPEC only. Three patients received only systemic chemotherapy. All patients with MCPM had only surgery. After a median follow‐up of seven years (2‐15), six patients (6/11; one death) with DMPM and two patients (two/three) with MCPM had a local and distant recurrences. Conclusion: Peritoneal mesothelioma in children is a rare condition with difficult diagnosis and high risk of recurrence. Worldwide interdisciplinary collaboration and networking are mandatory to help diagnosis and provide harmonious treatment guidelines.